Efficacy and Safety of Endovascular Treatment in Patients with Internal Carotid Artery Occlusion and Collateral Middle Cerebral Artery Flow - Kim, Yong-Won (J Korean Neurosurg Soc, 2019)
OBJECTIVE: In patients with internal carotid artery (ICA) occlusion, collateral middle cerebral artery (MCA) flow has a protective role against ischemia. However, some of these patients may experience initial major neurological deficits and major worsening on following days. Thus, we investigated the safety and efficacy of endovascular treatment (EVT) for ICA occlusion with collateral MCA flow by comparing clinical outcomes of medical treatment versus EVT. METHODS: The inclusion criteria were as follows : 1) acute ischemic stroke with ICA occlusion and presence of collateral MCA flow on transfemoral cerebral angiography (TFCA) and 2) hospital arrival within 12 hours from symptom onset. The treatment strategy was made by the attending physician based on the patient’s clinical status and results of TFCA. RESULTS: Eighty-one patients were included (30 medical treatment, 51 EVT). The EVT group revealed a high incidence of intracranial ICA occlusion, longer ipsilesional MCA contrast filling time, and a similar rate of favorable clinical outcome despite a higher mean baseline the National Institutes of Health Stroke Scale (NIHSS) score. By binary logistic regression analysis, intravenous recombinant tissue plasminogen activator and EVT were independent predictors of favorable clinical outcome. In subgroup analysis based on stroke etiology, the non-atherosclerotic group showed a higher baseline NIHSS score, higher incidence of EVT, and a higher rate of distal embolization during EVT in comparison with the atherosclerotic group. CONCLUSION: In patients with ICA occlusion and collateral MCA flow, decisions regarding treatment strategy based on TFCA can help achieve favorable clinical outcomes. EVT strategy with respect to etiology of ICA occlusion might help achieve better angiographic outcomes.